2014
DOI: 10.1589/jpts.26.785
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Neck Muscle Thickness Due to Differences in Intermittent Cervical Traction Force Measured by Ultrasonography

Abstract: [Purpose] Many patients receive intermittent cervical traction in a daily treatment setting. However, unified settings for traction force, duration, and direction have yet to be determined. Therefore, an objective index is required to determine changes in traction conditions or to indicate its effectiveness. [Subjects] Fifteen healthy males volunteers participated in this study. [Methods] The thickness of the trapezius and splenius capitis muscles before and during traction were measured using ultrasonography … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 7 publications
(8 reference statements)
0
7
0
Order By: Relevance
“…Recently, Katsushi 4 ) proposed that a traction force of a low intensity, such as 5 kg or 8 kg, did not significantly change the thickness of the upper trapezius; however he reported that a traction force of a high intensity at 11 kg might significantly decrease muscle thickness. In other words, when a relatively high traction force is given, changes in the upper trapezius may be triggered.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Recently, Katsushi 4 ) proposed that a traction force of a low intensity, such as 5 kg or 8 kg, did not significantly change the thickness of the upper trapezius; however he reported that a traction force of a high intensity at 11 kg might significantly decrease muscle thickness. In other words, when a relatively high traction force is given, changes in the upper trapezius may be triggered.…”
Section: Discussionmentioning
confidence: 99%
“…Katsushi 4 ) administered intermittent cervical traction in a reclining wheelchair composed of traction for 20 seconds and resting for 10 seconds with the cervical flexion angle at 10 degrees; meanwhile, we used the same sitting posture as that in a hospital but traction device’s cervical flexion angle was uncontrollable. Therefore, the differences between the two studies’s results are considered to have emerged from differences in the traction positions, cervical flexion angles, or types of traction devices.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations